Biofilme misto de Streptococcus pyogenes e Candida albicans: estabelecimento e validação de um modelo in vitro e comparação do efeito antibiofilme entre fármacos de referência e genéricos - Alves , Guilherme dos Santos Gomes (2024)
The objectives of the present study were to establish an in vitro model of dual-species biofilm of Streptococcus pyogenes and Candida albicans, validate this biofilm model through dose-response analysis after treatments with amoxicillin and nystatin, and compare the antibiofilm effects of reference and generic drugs. Biofilms were formed for 48 hours in 96-well plates and different variation factors were evaluated, including the culture medium (Brain Heart Infusion (BHI) broth or artificial saliva (AS)), the human salivary pellicle (present or absent), and the inoculation sequence of microorganisms. The resulting biofilms were analyzed by quantifying colony-forming units (CFUs), total biomass and metabolic activity. To validate one of the models, the mixed biofilm was treated with different concentrations of amoxicillin and nystatin, and biomass and metabolism were quantified. Comparisons of the antimicrobial effect of reference versus generic amoxicillin, and reference versus generic nystatin were also performed, first by determining the minimum inhibitory concentration (MIC) for planktonic cells and, subsequently, by analyzing the biomass and metabolism of the mixed biofilms. Data were analyzed by ANOVA and Tukey’s test or by Kruskal-Wallis and Student-Newman-Keuls’ tests, with a significance level of 5%. The type of culture medium was the only variation factor that affected the formation of mixed biofilms. Biofilms formed in AS showed significantly higher biomass than those formed in BHI broth (p < 0.001). An opposite trend was observed for metabolic activity, as metabolism was greater for biofilms formed in BHI broth (p < 0.001). The growth of C. albicans was not affected by the different factors, while the CFU counts of S. pyogenes were significantly lower for biofilms formed in AS. In validation assays, amoxicillin and nystatin showed dose-dependent reducing effects. Comparing reference and generic drugs, the two products showed the same MIC values (0.015 µg/mL for S. pyogenes and 4 µg/mL for C. albicans) and the same effectiveness in reducing the biomass and metabolism of the mixed biofilms. In conclusion, the model involving the inoculation of the two species at the same time, without prior exposure to salivary pellicle and using BHI broth as culture medium was validated, and would be the choice for future in vitro studies assessing the effects of antimicrobial agents on dual-species biofilms of S. pyogenes and C. albicans. Finally, reference and generic drugs (amoxicillin and nystatin) exhibited similar effects on the pathogens studied.